2022
DOI: 10.2147/vhrm.s367187
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Toward Hypertension Among Hypertensive Patients Residing in Lebanon

Abstract: Background and Objectives Hypertension (HTN) is a major health concern that leads to cardiovascular disease and premature death. Assessing HTN knowledge, attitude, and practice (KAP) is crucial for controlling HTN. This study aimed to determine HTN KAP among hypertensive patients residing in Lebanon. Methods This cross-sectional study involved 342 hypertensive patients. A questionnaire form was used to collect data related to patients’ characteristics. SPSS was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
2
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
3
9
2
2
Order By: Relevance
“…Nonetheless, in a study conducted by Sefah et al 5 , most of respondents (53.7%) belonged to the 20-29 age group. In contrast to earlier studies 9,10 , which reported a higher percentage of respondents having hypertension for more than ten years, we found that 127 patients (37.1%) had received a diagnosis of hypertension within the six months to a year, and 160 patients (46.6%) had received the diagnosis within the last one to five years.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, in a study conducted by Sefah et al 5 , most of respondents (53.7%) belonged to the 20-29 age group. In contrast to earlier studies 9,10 , which reported a higher percentage of respondents having hypertension for more than ten years, we found that 127 patients (37.1%) had received a diagnosis of hypertension within the six months to a year, and 160 patients (46.6%) had received the diagnosis within the last one to five years.…”
Section: Discussioncontrasting
confidence: 99%
“…Balanced diet 138(40.2%), managing physical and emotional stress 127(37.1%), decreased salt concentration in diet 194(56.6%). 137(39.9%) patients practiced exercise on a routine basis which included different exercises walking and jogging (104), cycling (24), gym and sports (9). It is evident from Table 4 that 224(65.3%) patients regularly took antihypertensive medication.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, most of the participants displayed good attitude to hypertension. A similar result was also reported by other studies [34][35]. However, there is a need for improvement in self-monitoring of blood pressure.…”
Section: Twosupporting
confidence: 90%
“…Pengetahuan responden mengenai hipertensi membantu dalam pengendalian tekanan darah hipertensi karena pengetahuan akan mempengaruhi sikap terkait hipertensi (Widowati et al 2023). Hasil ini sejalan dengan penelitian yang dilakukan di Lebanon, dimana sebagian besar penderita hipertensi (67,2%) memiliki sikap yang cukup mengenai hipertensi (Machaalani et al 2022). Sikap berkorelasi positif dengan pengetahuan.…”
Section: Menurut Hasil Pengamatan DI Lapangan Tingkatunclassified
“…Semakin baik pengetahuannya, semakin baik pula sikapnya terkait hipertensi. Tingkat pendidikan yang tinggi dan lama menderita hipertensi (>10 tahun) berkorelasi positif dengan sikap yang baik dari penderita hipertensi (Machaalani et al 2022).…”
Section: Menurut Hasil Pengamatan DI Lapangan Tingkatunclassified